Augmenting Human Appearance Through Technological Design Layers - Genç, Çağlar; Raudanjoki, Özge; Colley, Ashley; Häkkilä, Jonna (Frontiers in Computer Science, 2022)
Augmenting human appearance with the means of technology can focus on different layers attached to or around the body. In this article, we present a categorization of human appearance and expression, with augmenting skin and its appendages, clothing and textile, accessories, body parts, and digital aura around the body. We report a non-systematic review of related works in each category and discuss their means in expressing functional, hedonic, and social aspects. In conclusion, our study contributes design perspectives on augmenting human appearances, as well as reveals challenges and opportunities.